Poetry-Painting Affinity as Intersemiotic Translation - Jiang, Chengzhi. author. aut Link
XVII, 171 p. 17 illus.
Keywords: This book interprets the close intimacy between poetry and painting from the perspective of intersemiotic translation, by providing a systematic examination of the bilingual and visual representation of landscape in the poetry of Wang Wei, a high Tang poet who won worldwide reputation. The author’s subtle analysis ranges from epistemological issues of language philosophy and poetry translation to the very depths where the later Heidegger and Tao-oriented Chinese wisdom can co-work to reveal their ontological inter-rootedness through a two-level cognitive-stylisitc research methodology.